THU0140 COMORBIDITIES AMONG KOREAN WOMEN WITH RHEUMATOID ARTHRITIS IN CHILDBEARING YEARS: A NATIONWIDE POPULATION-BASED STUDY. (2nd June 2020) - Chung, M. K.; Lim, H. S.; Park, J. S.; Lee, C. H.; Lee, J.
Abstract : Background: Rheumatoid arthritis is a chronic systemic inflammatory disease known to be associated with many comorbidities. Many women with rheumatoid arthritis (RA) are diagnosed with the disease before completing childbearing, but the risk of comorbidities associated with RA among women in childbearing years is not known. Objectives: We aimed to investigate the risk of comorbidities among Korean women with RA in childbearing years. Methods: From National Health Insurance Service data of 2009-2016, containing inpatient and outpatient claim information for approximately 97% of the Korean population, we identified 20-44 year aged-women with RA and controls without rheumatic diseases such as RA, systemic lupus erythematosus, and ankylosing spondylitis. Prevalence of comorbidities including cancer (Ca), hypertension (HTN), hyperlipidemia (HLD), and diabetes mellitus (DM) were analyzed. The rheumatic diseases and comorbidities were defined by International Classification of Disease (ICD)-10 codes for disease classifications. The comorbidities associated with RA were defined by the ICD-10 codes presented after the RA diagnosis. Results: Total 23, 756 women with RA and 208, 941 controls were identified. Women with RA had significantly higher prevalence of all comorbidities analyzed compared with the controls (49.92% vs 25.58%, p<0.001). In women with RA, Ca (OR 1.14), DM (OR 1.22), HTN (OR 1.56), and HLD (OR 2.44) occurred significantly more often compared with the controls (p<0.001). Conclusion: During childbearing years, women with RA are more susceptible to comorbidities leading to a significant burden in this specific population of Korean women in childbearing years. References: [1]Dougados M: Comorbidities in rheumatoid arthritis. Current opinion in rheumatology 2016, 28(3):282-288. [2]Choi IA, Park SH, Cha HS, Park W, Kim HA, Yoo DH, Baek HJ, Lee SG, Lee YJ, Park YB et al: Prevalence of co-morbidities and evaluation of their monitoring in Korean patients with rheumatoid arthritis: comparison with the results of an international, cross-sectional study (COMORA). International journal of rheumatic diseases 2018, 21(7):1414-1422. Disclosure of Interests: None declared